PERANCANGAN DAN ANALISIS KINERJA PRIVATE CLOUD COMPUTING DENGAN LAYANAN INFRASTRUCTURE-AS-A-SERVICE (IAAS) - , I Gusti Ngurah Wikranta Arsa; , Dr.tech. Khabib Mustofa, S.Si., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Server machine is one of the main components in supporting and developing a web-based scientific work. The high price of the server to be the main obstacle in the student produced a scholarly work. Server configuration that can be done anywhere and anytime to be a fundamental desire, in addition to the booking engine is easy, fast, and flexible is also highly desirable. For that we need a system that can handle these problems. Cloud computing with Infrastructure-As-A-Serveice (IAAS) can provide a reliable infrastructure. To determine the performance of the system, we required a performance analysis of cloud server between conventional servers. Results of performance analysis of private cloud computing with Infrastructure-As-A-Service (IAAS) indicate that the cloud server performance comparison with conventional server is not too much different and the system resource usage level servers provide more leverage.